Impact of Metabolism on T-Cell Differentiation and Function and Cross Talk with Tumor Microenvironment - Kouidhi, Soumaya; Elgaaied, Amel Benammar; Chouaib, Salem (Frontiers in Immunology, 2017)
The immune system and metabolism are highly integrated and multilevel interactions between metabolic system and T lymphocyte signaling and fate exist. Accumulating evidence indicate that the regulation of nutrient uptake and utilization in T cells is critically important for the control of their differentiation, and manipulating metabolic pathways in these cells can shape their function and survival. This review will discuss some potential cell metabolism pathways involved in shaping T lymphocyte function and differentiation. It will also describes how subsets of T cells have specific metabolic requirements and signalling pathways that contribute to their respective function. Examples showing the apparent similarity between cancer cell metabolism and T cells during activation are illustrated and finally some mechanisms being used by tumour microenvironment to orchestrate T-cell metabolic dysregulation and the subsequent emergence of immune suppression are discussed. We believe that targeting T cell metabolism may provide an additional opportunity to manipulate T cell function in the development of novel therapeutics.